"Come and See": Uncovering Julian of Norwich's Teaching of Wonder in Revelations of Divine Love. (20th February 2022) - Scott, Jessica
Abstract: Julian of Norwich's Revelations of Divine Love contain within them two curious suggestions pertaining to sight. First, Julian's own ' goostely ' sight is presented in strikingly physical terms, such that her spiritual encounter with God is placed in parallel with what it is physically to see in the material world. Second, Julian insists throughout her text that her reader will be able to 'see' God without anywhere expositing what exactly this might mean. It is the argument of this essay that these two suggestions might be understood with reference to each other. Namely, Julian might have steeped her own invisible seeing in strikingly physical terms to indicate the particular capacity of our physical sight to perceive a correlate of the ' goostely ' sight of God she encounters. I discuss how the experience of perceiving wonder, through the physical senses, might be the reader's way to partake in her same sight of God. On the one hand, recognising the possible significance of such wonder for Julian enables us to understand more fully dimensions of her theology of embodiment. On the other, understanding 'wonder' against the theology she gives it offers us new resources with which to consider the significance of this experience.